INTERPRETATION OF SELF-POTENTIAL DATA AROUND THE FIELD OF EAST HALL BANDUNG INSTITUTE OF TECHNOLOGY TO DETERMINE THE SUBSURFACE ANOMALY - Kemala Sari, Annisa
The self-potential (SP) method is one of the geophysical methods that works by measuring static natural voltage present in a group of points on the ground surface. This method is passive, as it utilizes measurements of naturally occurring potential differences without injecting electric currents through the ground surface. The purpose of this research is to determine the distribution of potential values, identify the direction of subsurface fluid flow, determine the geometric shape, and the depth of the anomaly source in the research area. Data acquisition is performed using a fixed-based electrode method with 11 measurement lines and a total of 165 points. The distance between points is 2.5 meters, and the distance between measurement lines is 5 meters. The obtained electric potential data is then qualitatively interpreted using SURFER 13 application to generate isopotential contour of the research area, with the lowest value is -110 mV and the highest value is 130 mV. Based on the isopotential contour and topographic effects, it can be predicted that fluid flow occurs from the north to the south in the research area. Subsequently, quantitative interpretation is conducted by performing forward modelling and inverse modelling in MATLAB, which reveals that the subsurface anomaly appears as a horizontal cylinder with a depth of 4.53 meters.